The Effect of Synbiotic Shake on Blood Glucose and Lipid Profile in Hyperglycemia Wistar Rats - Lily Arsanti Lestari; Inas Nur Hafizhah; Happy Nurlita Octavinanda; Latifah Mahdiyati; Refdiana Dewi; Perdana Samekto Tyasnugroho Suyoto; Emy Huriyati; Sunarti (Journal of Food and Pharmaceutical Sciences, 2020)
Several studies found that the probiotic bacterias such as Lactobacillus acidophilus La5 and Bifidobacterium lactis Bb12 could prevent glycemia and control the blood lipid profiles. Currently, a probiotic product such as yogurt is not preferable by some consumers since the taste is sour. Therefore, this study was conducted to develop milkshakes supplemented by probiotics Lactobacillus acidophilus La5 and Bifidobacterium lactis Bb12 which are expected to be more acceptable and have a beneficial effect with the addition of prebiotics and soluble fiber glucomannan. This study aims to determine the effect of synbiotic shakes on fasting blood glucose levels and lipid profiles in hyperglycemia Wistar rat models. The study design was a pre-posttest controlled group with 48 male Wistar rats divided into 8 groups, namely the healthy control group (I); hyperglycemia control group (II); group III that received metformin; group IV that received synbiotic shake with La5 + FOS; group V that received synbiotic shake La5 + inulin; group VI that received synbiotic shake Bb12 + FOS; group VII that received synbiotic shake Bb12 + inulin; and group VIII that received synbiotic shake La5 + Bb12 + FOS. The dose of the intervention was 3.6 ml/day with an intervention duration of 28 days. The results showed that the differences in blood glucose levels were not significant (p> 0.05) except for groups IV and VI that experienced a significant increase (p <0.05). The differences in lipid profiles showed insignificant changes in LDL levels except in groups IV and V, a significant increase in HDL levels (p <0.05) in group V and VI, and insignificant change in triglycerides except in group VI. It can be concluded that the administration of synbiotic shakes with a variety of prebiotics Lactobacillus acidophilus La5 and Bifidobacterium lactis Bb12 for 4 weeks were able to maintain fasting blood glucose levels and lipid profiles in hyperglycemic rats.